Modal Analysis Of Blended Wing-Body UAV - Neno Ruseno (FTK UNSURYA, 2021)
The modal analysis deals with the dynamic behavior of mechanical structures under the dynamic vibration. This study aims to analyze the vibration characteristic of the blended wing-body Unmanned Aerial Vehicle (UAV) using modal analysis. The numerical method is used to calculate the eigen frequencies of the system. The COMSOL Multiphysics is selected as the Finite Element Method (FEM) software to simulate the study. The resulted eigen frequencies are 278.05 Hz, 721.28 Hz, 816.39 Hz, 1601.7 Hz, 1699.5 Hz, and 1855.5 Hz. The study also evaluates the displacement of the leading edge of the wing in all axes to understand the modal shapes. The modal shapes found are updrift, swift back, flapping vertical, flapping horizontal, flapping opposite horizontal and flapping more wave in horizontal movement. The comparison of resulted eigen frequencies with a conventional aircraft wing is conducted to understand the difference in its vibration characteristics.